2002
DOI: 10.1074/jbc.m202261200
|View full text |Cite
|
Sign up to set email alerts
|

MEK Mediates v-Src-induced Disruption of the Actin Cytoskeleton via Inactivation of the Rho-ROCK-LIM Kinase Pathway

Abstract: Organization of actin filaments is controlled by the Rho family of small GTPases, Rho, Rac, and Cdc42 (1). Among them, Rho regulates the assembly of actin stress fibers and focal contacts, through activation of the downstream effectors mDia and the closely related kinases ROCKI and ROCKII (2, 3). Activation of ROCK by Rho is implicated in stress fiber and focal contact formation (2, 4). ROCK increases the phosphorylation of myosin light chains by directly phosphorylating myosin light chains and negatively regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 33 publications
11
67
4
Order By: Relevance
“…ROCK activates LIMK which phosphorylates cofilin, inhibiting its actin-depolymerizing activity, thereby stabilizing actin stress fibers. Consistent with our findings, v-Src inhibited cofilin phosphorylation and the mechanism involved a MEK-dependent and PI3 kinase-independent pathway (Pawlak and Helfman, 2002). Rho mutants restore stress fiber formation in v-Src-transformed cells (Mayer et al, 1999), consistent with a model in which Rho proteins serve as downstream targets of v-Src.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…ROCK activates LIMK which phosphorylates cofilin, inhibiting its actin-depolymerizing activity, thereby stabilizing actin stress fibers. Consistent with our findings, v-Src inhibited cofilin phosphorylation and the mechanism involved a MEK-dependent and PI3 kinase-independent pathway (Pawlak and Helfman, 2002). Rho mutants restore stress fiber formation in v-Src-transformed cells (Mayer et al, 1999), consistent with a model in which Rho proteins serve as downstream targets of v-Src.…”
Section: Discussionsupporting
confidence: 78%
“…c-Src inhibits ROCK II activity (Pawlak and Helfman, 2002). We therefore examined the relative abundance of c-Src, in c-jun Ϫ/Ϫ and wt 3T3 cells.…”
Section: C-jun Induction Of Migration Is Dependent On Rock and Src Kimentioning
confidence: 99%
“…However, calpain has numerous other targets, including both signaling and structural proteins within the focal adhesion plaque, suggesting that calpain could mediate focal adhesion turnover through a variety of mechanisms (68 -70). In addition to epidermal growth factor signaling, sustained ERK activation during cellular transformation by oncogenic Ras and v-Src stimulates focal adhesion disassembly by uncoupling the RhoA-ROCK pathway (71,72). TSP1 stimulates a biphasic activation of ERK, with both an early peak in ERK activity at 10 min and a late peak in ERK activity at 2 h following treatment (42).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin activation of MAPK requires c-Src and FAK, and ERK activity is required for FAK stimulated focal adhesion disassembly to promote cell migration [79,89]. Several studies have shown that FAK or v-Src can suppress the activities of Rho [48,87] and its effector, ROCK [88], and this pathway requires ERK signaling [79,104] to modulate actin and focal adhesion dynamics. Consistent with these observations, activated FAK and c-Src and activated ERK localize to focal adhesions [89].…”
Section: Erk Regulation Of Rho-rock Functionmentioning
confidence: 99%